Diabetes mellitus and hyperglycemia in patients with rheumatoid arthritis - L. V. Kondratyeva; T. A. Panafidina; E. V. Gerasimova; Yu. N. Gorbunova; T. V. Popkova; E. L. Nasonov (Современная ревматология, 2014)
Proinflammatory cytokines involved in the pathogenesis of rheumatoid arthritis (RA) are able to inhibit the production of insulin and to cause insulin resistance in peripheral tissues. Conceivably RA increases the risk of developing carbohydrate metabolic disturbances (CMDs), such as diabetes mellitus (DM), fasting hyperglycemia (FH), and impaired glucose tolerance. Patients with a concurrence of RA and DM belong to a category of the most critically ill patients with a poor prognosis of macro- and microvascular complications.Objective: to estimate the rate of CMDs (DM and FH) in a cohort of patients with RA and their possible impact on the course of arthritis.Subjects and methods. The investigation enrolled 165 patients (28 men and 137 women) aged 55 [47; 61] years who were diagnosed with RA and followed up at the V.A. Nasonova Research Institute of Rheumatology. The patients who were seropositive for rheumatoid factor and anti-cyclic citrullinated peptide antibodies were 86.3 and 78.8%, respectively. RA activity was low in 29.1% of the patients, moderate in 48.5%, and high in 22.4%. Glucocorticoids (GC) were taken at a mean dose of 5 [5; 7.5] mg/day by 40.6% of the patients; methotrexate, leflunomide, and genetically engineered biological agents were used by 72.7, 8.5, and 23.7%, respectively. A survey was conducted among the patients to find out their awareness of the presence of CMDs and fasting venous plasma glucose levels were determined to screen for hyperglycemia. Height and weight were measured and body mass index (BMI) was calculated.Results. CMDs were present in 21 (12.7%) of the 165 patients with RA. Only 11 (6.7%) of the 165 patients were aware of having DM (2 cases with type 1 DM and 9 with type 2 DM); laboratory tests revealed CMDs in the remaining 10 patients (8 cases with FH and 2 with type 2 DM). The patients with DM and FH had a large number of tender joints (TJN) and high scores of general health survey (GHS) and DAS28 than those with normal blood glycose levels, but did not differ in RA duration, acute-phase indicators (erythrocyte sedimentation rate, C-reactive protein), and the number of swollen joints. Fifty-seven (34.5%) patients were overweight and 39 (23.6%) were obese. In the patients who took GC, glucose levels were lower (5.1 [4.7; 5.5]) than in those who did not (5.4 [5.0; 5.9] mmol/l; p = 0.001) and correlated with BMI ((r = 0.3; p = 0.01).Conclusion. The investigation demonstrated the high rate of DM and FH in RA, but low patient awareness of these conditions, as well as the relationship of CMDs to arthritis activity mainly due to the changes of subjective indices (GHS and TJN). The intake of GC and BMI may affect blood glucose levels in RA.